The Examination of the Reasons for the Need to Change and Integrate in the Dental Curriculum in Iran and the World - Safarnavadeh, Maryam; Ebrahimpour Koumleh, Samira; Jafari, Soudeh (Journal of Dental School, 2018)
Objectives The aim of this research was to examine the reasons for the need to change and bring about integration in the dental curriculum in Iran and worldwide. Methods The qualitative method was used in this research. The real experiences of some reliable universities over the world and in Iran were studied on the necessity to change the dental curriculum and the integrated curriculum through library studies. In addition, the information obtained from this study was analyzed and interpreted based on the theoretical reasoning and empirical achievements of the authoritative and reliable universities. Results The result of the examination of these experiences of the various universities on the modification and integration of the dental curriculum showed that the high cost of education in this discipline and dissatisfaction of the students with the teaching methods in this field were among the most important reasons for the change in the dental curriculum in Iran and globally. The integrated pattern of the curriculum of the universities was associated with the positive consequences on the review and applied changes in the dental curriculum. Conclusion In total, the axis of the activities of changing and modifying the curriculum in these universities was established by the focus on the integrated approaches, including " educating research", "the evidence-based dental”, and "entering new knowledge in the dental curriculum".